Management of hypoplastic left heart syndrome with intact atrial septum: a two-centre experience. (8th September 2015) - Sathanandam, Shyam K.; Philip, Ranjit; Gamboa, David; Van Bergen, Andrew; Ilbawi, Michel N.; Knott-Craig, Christopher; Waller, B. Rush; Javois, Alexander J.; Cuneo, Bettina F.
Abstract: Introduction: Hypoplastic left heart syndrome with an intact atrial septum is a poor predictor of outcomes. Prenatal assessment of pulmonary venous Doppler and emergent postnatal cardiac intervention may be associated with better outcomes. Materials and methods: A retrospective review of all hypoplastic left heart syndrome patients in two centres over a 5-year period was performed. Group 1 included patients with adequate inter-atrial communication. Group 2 included patients with prenatal diagnosis with an intact atrial septum who had immediate transcatheter intervention. Group 3 included patients with intact atrial septum who were not prenatally diagnosed and underwent either delayed intervention or no intervention before stage 1 palliation. Primary outcome was survival up to stage 2 palliation. Results: The incidence of hypoplastic left heart syndrome with a restrictive atrial communication was 11.2% (n=19 of 170). Overall survival to stage 2 or heart transplantation was 85% and 67% for Groups 1 and 2, respectively (n=129/151, n=8/12; p=0.03), and 0% (n=0/7) for Group 3. Survival benefits were observed between Groups 2 and 3 (p<0.001). Foetal pulmonary vein Doppler reverse/forward velocity time integral ratio of ⩾18% (sensitivity, 0.99, 95% CI, 0.58–1; specificity, 0.99, 95% CI, 0.96–1) was predictive of the need for emergent left atrial decompression. Conclusion: Using a multidisciplinary approach and foetal pulmonary vein Doppler, time-saving measures can be instituted by delivering prenatally diagnosed neonates with hypoplastic left heart syndrome with intact atrial septum close to the cardiac catheterisation suite where left atrial decompression can be performed quickly and safely that may improve survival.